Model Load Tests on Geotextile Reinforced Embankments - Kato, Toshiaki; Aoyama, Noriaki; Takeuchi, Tatsunori; Yasunaga, Hiroyuki (Proceedings of geotextile symposium, 1986)
Most of design methods for geotextile reinforced embankments are based on only equilibrium of moment or earth pressure in the critical state, but deformation behaviour has to be taken into account. This paper describes model load tests on geotextile reinforced embankments filled in a small box. And the influence of the kind and length of geotextile on bearing capacity and deformation behaviour was investigated. It was found that considerable deformation occures before it reaches the critical state, and that restraint of deformation can't be estimated only by ultimate tensile strength of geotextile.